Chemo‐Enzymatic Synthesis and Antimicrobial Evaluation of Alkyloxy Propanol Amine‐Based Cationic Ether Lipids. (23rd November 2012) - Reddy, J. R. C.; Rao, B. V. S. K.; Karuna, M. S. L.; Kumar, K. P.; Murthy, U. S. N.; Prasad, R. B. N.
Abstract: The present study involved the synthesis and antimicrobial evaluation of alkyloxy propanol amine‐based cationic lipids N, N ‐dimethyl‐1‐octadecylamino‐3‐alkyloxy‐2‐propanol (series A, 7a–e) and N ‐methyl‐ N, N ‐di‐(2‐hydroxy‐3‐alkyloxy‐2 propyl) octadecylamine (series B, 9a–e) and their acetylated derivatives (8a–e and 10a–e). A simple three‐step chemo‐enzymatic approach was employed for the synthesis of 7a–e and 9a–e in 71–80 and 67–88 % yields, respectively. The first step involved the synthesis of a series of glycidyl ethers from a series of alcohols (C4, C8, C10, C12, C14 ) which were opened in the second step with octadecylamine to obtain 1‐octadecylamino‐3‐alkyloxy‐2 propanol (5a–e) and N, N ‐di‐(2‐hydroxy‐3‐alkyloxypropyl) octadecylamine (6a–e). In the third step, alkyloxy propanolamines (5a–e, 6a–e) were quaternized using methyl iodide to yield quaternized ammonium salts. The quaternized ammonium salts were enzymatically acetylated using Candida antarctica lipase‐B based immobilized enzyme Novozym 435 to obtain their acetylated derivatives. The quaternized salts as well as their acetylated derivatives were evaluated for antibacterial and antifungal properties. The title compounds were found to possess moderate to good antibacterial activities against all the studied bacterial strains namely, Bacillus subtilis, Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa and Klebsiella aerogenes compared to streptomycin and cetyl trimethyl ammonium bromide (CTAB). The title compounds exhibited relatively good antifungal activities against Candida albicans and no significant activities against other fungal strains namely, Saccharomyces cerevisiae, Rhizopus oryzae and Aspergillus niger when compared to amphotericin B and CTAB.